Programming Ruby 1.9 the pragmatic programmers' guide - Thomas, David 1956-; Fowler, Chad; Hunt, Andrew 1964- (Raleigh, N.C. Pragmatic Bookshelf, 2009)
Ruby 1.9 is the latest version of Ruby. It has many compelling features, including multinationalization support, new block scoping, and better performance. At the same time, the current Ruby 1.8 is still being maintained and is widely used. Ruby is a fully object-oriented language, much like the classic object-oriented language, Smalltalk. Like Smalltalk, it is dynamically typed (as opposed to Java or C++), but unlike Smalltalk, Ruby features the same conveniences found in modern scripting languages, making Ruby a favorite tool of intelligent, forward-thinking programmers and the basis for the Rails web framework. This is the reference manual for Ruby, including a description of all the standard library modules, a complete reference to all built-in classes and modules (including all the new and changed methods introduced by Ruby 1.9). It also includes all the new and changed syntax and semantics introduced since Ruby 1.8. Learn about the new parameter passing rules, local variable scoping in blocks, fibers, and the new block declaration syntax, among other exciting new features.
Getting started -- Ruby.new -- Classes, objects, and variables -- Containers, blocks, and iterators -- Sharing functionality: inheritance, modules, and mixins -- Standard types -- Regular expression -- More about methods -- Expressions -- Exceptions, catch, and throw -- Basic input and output -- Fibers, threads, and processes -- Unit testing -- When trouble strikes -- Ruby and its world -- Namespaces, source files, and distribution -- Character encoding -- Interactive Ruby shell -- Documenting Ruby -- Ruby and the web -- Ruby and Microsoft Windows -- The Ruby language -- Duck typing -- Metaprogramming -- Reflection, objectspace, and distributed Ruby -- Locking Ruby in the safe -- Built-in classes and modules -- Standard library -- Extending Ruby.
Includes bibliographical references and index.
E2-1423G donated by Mr. Jeff Kwong.
Keywords: Ruby (Computer program language)